Associations between high triglycerides and arterial stiffness in a population-based sample: Kardiovize Brno 2030 study - Iuliia Pavlovska; Sarka Kunzova; Juraj Jakubik; Jana Hruskova; Maria Skladana; Irma Magaly Rivas-Serna; Jose R. Medina-Inojosa; Francisco Lopez-Jimenez; Robert Vysoky; Yonas E. Geda; Gorazd B. Stokin; Juan P. González-Rivas (Lipids in Health and Disease, 2020)
Abstract Background The term arterial stiffness (ArSt) describes structural changes in arterial wall related to the loss of elasticity and is known as an independent predictor of cardiovascular diseases (CVD). The evidence relating to ArSt and triglycerides (TG) shows contradictory results. This paper means to survey the association between high TG and ArSt, utilizing the cardio-ankle vascular index (CAVI). Methods Subjects aged between 25 and 64 years from a random population-based sample were evaluated between 2013 and 2016. Data from questionnaires, blood pressure, anthropometric measures, and blood samples were collected and analyzed. CAVI was measured using VaSera VS-1500 N devise. Subjects with a history of CVD or chronic renal disease were excluded. Results One thousand nine hundred thirty-four participants, 44.7% of males, were included. The median age was 48 (Interquartile Range [IQR] 19) years, TG levels were 1.05 (0.793) mmol/L, and CAVI 7.24 (1.43) points. Prevalence of high CAVI was 10.0% (14.5% in males and 6.4% in females; P <  0.001) and prevalence of hypertriglyceridemia was 20.2% (29.2% in males and 13% in females, P <  0.001). The correlation between TG and CAVI was 0.136 (P <  0.001). High CAVI values were more prevalent among participants with metabolic syndrome (MetS), high blood pressure, dysglycemia, abdominal obesity, high LDL-cholesterol (LDL-c), and high total cholesterol. Using binary regression analysis, high TG were associated with high CAVI, even after adjustment for other MetS components, age, gender, smoking status, LDL-c, and statin treatment (β = 0.474, OR = 1.607, 95% CI = 1.063–2.429, P = 0.024). Conclusion TG levels were correlated with ArSt, measured as CAVI. High TG was associated with high CAVI independent of multiple cardiometabolic risk factors. Awareness of the risks and targeted treatment of hypertriglyceridemia could further benefit in reducing the prevalence of CVD and events.